Hirnantian (latest Ordovician) bio- and chemostratigraphy of the Stirnas-18 core, western Latvia - Hints, Linda; Hints, Olle; Kaljo, Dimitri; Kiipli, Tarmo; Männik, Peep; Nõlvak, Jaak; Pärnaste, Helje (Estonian Journal of Earth Sciences, 2010)
Integrated study of the uppermost Ordovician Porkuni Stage in the Stirnas-18 core, western Latvia, has revealed one of the most complete Hirnantian successions in the eastern Baltic region. The interval is characterized by two shallowing upwards depositional sequences that correspond to the Kuldiga and Saldus formations. The whole-rock carbon stable isotope curve indicates a long rising segment of the Hirnantian carbon isotope excursion, with the highest peak in the upper part of the Kuldiga Formation. The bioclast carbon and oxygen curves fit well with the whole-rock carbon data. Micro- and macrofossil data enabled seven combined associations to be distinguished within the Hirnantian strata. The early Porkuni fauna of the Spinachitina taugourdeaui Biozone, with pre-Hirnantian affinities, is succeeded by an interval with a Hindella–Cliftonia brachiopod association, a specific polychaete fauna, the chitinozoan Conochitina scabra, and the conodont Noixodontus girardeauensis. The middle part of the Kuldiga Formation is characterized by a low-diversity Dalmanella testudinaria brachiopod association, high diversity of scolecodonts, and the occurrence of the chitinozoan Lagenochitina prussica. From the middle part of the Kuldiga Formation the youngest occurrence yet known of the conodont Amorphognathus ordovicicus is reported. Also typical of the Kuldiga Formation is the occurrence of the trilobite Mucronaspis mucronata. The uppermost Hirnantian Saldus Formation contains no shelly fauna, but yields redeposited conodonts and at least partly indigenous chitinozoans and scolecodonts. Palaeontological criteria and stable isotope data enable correlation of the Stirnas section with other Hirnantian successions in the Baltic region and elsewhere.